Formation of Hydrophilic Nanofibers from Nanostructural Design in the Co-Encapsulation of Celecoxib through Electrospinning - Kedi Chu; Yi Zhu; Geng Lu; Sa Huang; Chuangzan Yang; Juying Zheng; Junming Chen; Junfeng Ban; Huanhuan Jia; Zhufen Lu (MDPI AG, 2023)
This study presents a method for a one-step co-encapsulation of PLGA nanoparticles in hydrophilic nanofibers. The aim is to effectively deliver the drug to the lesion site and achieve a longer release time. The celecoxib nanofiber membrane (Cel-NPs-NFs) was prepared by emulsion solvent evaporation and electrospinning with celecoxib as a model drug. By this method, nanodroplets of celecoxib PLGA are entrapped within polymer nanofibers during an electrospinning process. Moreover, Cel-NPs-NFs exhibited good mechanical strength and hydrophilicity, with a cumulative release of 67.74% for seven days, and the cell uptake at 0.5 h was 2.7 times higher than that of pure nanoparticles. Furthermore, pathological sections of the joint exhibited an apparent therapeutic effect on rat OA, and the drug was delivered effectively. According to the results, this solid matrix containing nanodroplets or nanoparticles could use hydrophilic materials as carriers to prolong drug release time.